Interpreting Sustainability Using Robert Pirsig’s Levels of Quality - Venkatesh, G. (Problemy Ekorozwoju, 2011)
Quality, according to writer Robert Pirsig (of Zen and the Art of Motorcycle Maintenance fame), is essentially goodness which humans should comprehend, appreciate and strive towards. It is the understanding or the comprehension he stresses on, in the said book, as a sine qua non for the success of any undertaking towards Quality. Sustainable Development is a Quality; a desirable one at that! Pirsig breaks up Quality into different hierarchical levels – Natural, Biological, Social, Intellectual and Mystic, in that ascending order of importance. He believes that when the Quality levels on the lower rungs start running amok and developing merely for their own sakes, without striving to bring about progress – visualised as being superior to mere growth and development, the mystics need to step in and create awareness of one’s true purpose in life. This essay is not an esoteric, metaphysical mini-treatise. It is also not just a book review, but an interpretation of the thoughts Pirsig has so wonderfully put into words in his book – LILA: An Enquiry into Morals.